Laminate and precursor laminate
By designing the first and second crosslinking layers in the composite material, containing crosslinked fluorine content copolymers with different unit combinations, and ensuring that the mass fraction of the crosslinked product reaches 85% or more, the problem of poor dimension stability in the composite material under high temperature environment is solved, and better thermal stability is achieved.
Patent Information
- Application Number
- JP2022017181
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-02-07
- Publication Date
- 2025-03-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The current composite materials using fluorine content copolymers have poor dimension stability and are prone to shrink in high temperature environments.
A composite material consisting of the first and second crosslinking layers is used, wherein the first crosslinking layer contains the fluorine content copolymer A1 of the crosslinking product, and the second crosslinking layer contains the fluorine content copolymer B1 of the crosslinking product, and the unit combinations of the two are different, and the mass fraction of the crosslinking product reaches 85% or more.
It significantly improves the dimensional stability of composite materials in high temperature environments and reduces heat shrinkage.
Smart Images

Figure 2025038259000001 
Figure 2025038259000002 
Figure 2025038259000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a precursor laminate. [Background technology]
[0002] Fluorine-containing copolymers are used in a variety of fields because of their excellent heat resistance, chemical resistance, oil resistance, weather resistance, electrical insulation, etc. Fluorine-containing copolymers are sometimes used by laminating them with various polymers. Patent Document 1 discloses a laminate using a fluorine-containing copolymer, which has a rubber layer (1) containing a fluorine-containing rubber and an acrylic rubber, and a rubber layer (2) containing a fluorine-containing rubber. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 98 / 036901 Summary of the Invention [Problem to be solved by the invention]
[0004] Laminates using fluorine-containing copolymers are sometimes used not only in low-temperature environments but also in high-temperature environments, and therefore are required to have heat resistance. When the present inventors evaluated a laminate such as that described in Patent Document 1, they found that there was room for improvement in dimensional stability after use in a high-temperature environment, which is considered to be one aspect of heat resistance. Specifically, when a laminate such as that described in Patent Document 1 was used in a high-temperature environment, the layers constituting the laminate sometimes shrunk.
[0005] The present invention has been made in view of the above problems, and an object of the present invention is to provide a laminate having excellent dimensional stability after use in a high-temperature environment, and a precursor laminate thereof which is an uncrosslinked product thereof. [Means for solving the problem]
[0006] As a result of intensive research into the above-mentioned problems, the present inventors have found that in a laminate having a first crosslinked layer containing a fluorine-containing copolymer A and optionally a non-fluorine polymer, and a second crosslinked layer containing a fluorine-containing copolymer B and optionally a non-fluorine polymer, CA and the content M of the crosslinked product of the fluorine-containing copolymer B CB It has been found that when both of these are equal to or greater than specific values, the dimensional stability after use in a high-temperature environment is excellent, and this has led to the present invention.
[0007] That is, the present inventors have found that the above problems can be solved by the following configuration. [1] A laminate having a first crosslinked layer and a second crosslinked layer disposed on the first crosslinked layer, the first crosslinked layer contains a crosslinked product of a fluorinated copolymer A1 and optionally contains a crosslinked product of a non-fluorinated polymer A2, the second crosslinked layer contains a crosslinked product of a fluorine-containing copolymer B1 and optionally contains a crosslinked product of a non-fluorine-containing polymer B2, a combination of units based on monomers constituting the fluorinated copolymer A1 and a combination of units based on monomers constituting the fluorinated copolymer B1 are different from each other, The content M of the crosslinked product of the fluorocopolymer A1 relative to the total of the crosslinked product of the fluorocopolymer A1 and the crosslinked product of the non-fluoropolymer A2 CA is 85% by mass or more, The content M of the crosslinked product of the fluorine-containing copolymer B1 relative to the total of the crosslinked product of the fluorine-containing copolymer B1 and the crosslinked product of the non-fluorine-containing polymer B2 CB is 85 mass % or more. [2] Said M CA and the aforementioned M CB The laminate according to [1], wherein the absolute value of the difference between [3] The fluorine-containing copolymer A1 contains units based on vinylidene fluoride, The laminate according to [1] or [2], wherein the fluorine-containing copolymer B1 contains a unit based on tetrafluoroethylene and a unit based on propylene. [4] The laminate according to any one of [1] to [3], wherein at least one of the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom. [5] The laminate according to any one of [1] to [4], wherein the glass transition temperatures of the fluorocopolymer A1 and the fluorocopolymer B1 are both 15° C. or lower. [6] The laminate according to any one of [1] to [5], wherein at least one of the first crosslinked layer and the second crosslinked layer further contains a sintered body of diatomaceous earth and silica. [7] The first crosslinked layer does not contain a crosslinked product of the non-fluorinated polymer A2, The laminate according to any one of [1] to [7], wherein the second crosslinked layer does not contain a crosslinked product of the non-fluorinated polymer B2. [8] A precursor laminate having a first composition layer and a second composition layer disposed on the first composition layer, the first composition layer comprises a fluorine-containing copolymer A1 and a crosslinking agent, and optionally comprises a non-fluorine-containing polymer A2; the second composition layer comprises a fluorine-containing copolymer B1 and a crosslinking agent, and optionally comprises a non-fluorine-containing polymer B2; a combination of units based on monomers constituting the fluorinated copolymer A1 and a combination of units based on monomers constituting the fluorinated copolymer B1 are different from each other, The content M of the fluorine-containing copolymer A1 relative to the total of the fluorine-containing copolymer A1 and the non-fluorine-containing polymer A2 PA is 85% by mass or more, The content M of the fluorine-containing copolymer B1 relative to the total of the fluorine-containing copolymer B1 and the non-fluorine-containing polymer B2 PB is 85 mass % or more. [9] Said M PA and the aforementioned M PB The precursor laminate according to [8], wherein the absolute value of the difference between
[10] The fluorine-containing copolymer A1 contains units based on vinylidene fluoride, The precursor laminate according to [8] or [9], wherein the fluorine-containing copolymer B1 contains a unit based on tetrafluoroethylene and a unit based on propylene.
[11] The precursor laminate according to any one of [8] to
[10] , wherein at least one of the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom.
[12] The precursor laminate according to any one of [8] to
[11] , wherein the glass transition temperatures of the fluorocopolymer A1 and the fluorocopolymer B1 are both 15° C. or lower.
[13] The precursor laminate according to any one of [8] to
[12] , wherein at least one of the first composition layer and the second composition layer further contains a sintered body of diatomaceous earth and silica.
[14] The first composition layer does not contain the non-fluorinated polymer A2, The precursor laminate according to any one of [8] to
[13] , wherein the second composition layer does not contain the non-fluorinated polymer B2. Effect of the Invention
[0008] According to the present invention, it is possible to provide a laminate having excellent dimensional stability even after use in a high-temperature environment, and a precursor laminate which is an uncrosslinked product thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The terms used in the present invention have the following meanings. A numerical range expressed using "~" means a range including the numerical values before and after "~" as the upper and lower limits. In the numerical ranges described in stages in this specification, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples. In the present specification, each component may be used alone or in combination of two or more substances corresponding to each component. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. As used herein, a combination of two or more preferred embodiments is a more preferred embodiment. The term "unit" refers collectively to an atomic group derived from one molecule of a monomer that is formed directly by polymerization of the monomer, and an atomic group obtained by chemically converting a part of the atomic group. Hereinafter, a "unit based on a monomer" will also be simply referred to as a "unit". "Rubber" means rubber exhibiting properties defined by JIS K 6200:2008, and is to be distinguished from "resin". "Glass transition temperature" is the midpoint glass transition temperature as measured by differential scanning calorimetry (DSC). "Glass transition temperature" is also called "Tg."
[0010] [Laminate] The laminate of the present invention (hereinafter also referred to as "the laminate") is a laminate having a first crosslinked layer and a second crosslinked layer disposed on the first crosslinked layer, wherein the first crosslinked layer comprises a crosslinked product of fluorine-containing copolymer A1 and optionally a crosslinked product of non-fluorine-containing polymer A2, and the second crosslinked layer comprises a crosslinked product of fluorine-containing copolymer B1 and optionally a crosslinked product of non-fluorine-containing polymer B2. In the present laminate, the combination of units based on monomers constituting the fluorocopolymer A1 is different from the combination of units based on monomers constituting the fluorocopolymer B1. In the present laminate, the content M of the crosslinked product of the fluorocopolymer A1 relative to the total of the crosslinked product of the fluorocopolymer A1 and the crosslinked product of the non-fluoropolymer A2 is CA is 85% by mass or more, and the content M of the crosslinked product of the fluorocopolymer B1 relative to the total of the crosslinked product of the fluorocopolymer B1 and the crosslinked product of the non-fluoropolymer B2 is CB is 85 mass % or more.
[0011] The laminate has excellent dimensional stability even after use in a high temperature environment. The crosslinked fluorine-containing copolymer has excellent heat resistance, so CA and M CB It is presumed that because each of these is 85 mass % or more, the thermal shrinkage of the first crosslinked layer and the second crosslinked layer is sufficiently small, resulting in small dimensional change after storage of this laminate in a high-temperature environment.
[0012] [First crosslinked layer] The first crosslinked layer contains a crosslinked product of a fluorine-containing copolymer A1, and optionally contains a crosslinked product of a non-fluorine-containing polymer A2.
[0013] <Fluorine-containing copolymer A1> Fluorine-containing copolymer A1 is a copolymer having fluorine atoms and containing units based on two or more types of monomers, and exhibits rubber properties through crosslinking, i.e., the crosslinked product of fluorine-containing copolymer A1 exhibits rubber properties.
[0014] From the viewpoints of excellent fuel permeation resistance and excellent rubber properties in a low-temperature environment, the fluorine-containing copolymer A1 preferably contains vinylidene fluoride (hereinafter also referred to as "VdF") units, more preferably contains VdF units and hexafluoropropylene (hereinafter also referred to as "HFP") units, and further preferably contains VdF units, tetrafluoroethylene (hereinafter also referred to as "TFE") units and HFP units.
[0015] The fluorine-containing copolymer A1 may have a unit based on a monomer other than the above (hereinafter also referred to as "other monomer"). Specific examples of the other monomer include a monomer having two or more polymerizable unsaturated bonds (hereinafter also referred to as "monomer a"), chlorotrifluoroethylene (hereinafter also referred to as "CTFE"), 2,3,3,3-tetrafluoropropene (HFO-1234yf), (Z)-1-chloro-2,3,3,3,-tetrafluoropropene (HCFO-1224yd(Z)), perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE"), a monomer represented by the following formula (5), ethylene, and propylene. In addition, a monomer having a halogen atom (hereinafter also referred to as "monomer having another halogen atom") that is a monomer other than the above may also be mentioned.
[0016] Specific examples of the polymerizable unsaturated bond include a carbon atom-carbon atom double bond (C=C) and a carbon atom-carbon atom triple bond (C≡C). The number of polymerizable unsaturated bonds in the monomer a is preferably from 2 to 6, more preferably 2 or 3, and particularly preferably 2, in terms of superior polymerization reactivity. It is preferable that the monomer a further contains a fluorine atom.
[0017] The monomer a is preferably a monomer represented by formula (1). (CR 11 R 12 =CR 13 ) a1 R 14 (1) In formula (1), R 11 , R 12 and R 13 each independently represents a hydrogen atom, a fluorine atom, a methyl group, or a trifluoromethyl group; a1 represents an integer of 2 to 6; R 14 represents a1-valent perfluorohydrocarbon group having 1 to 10 carbon atoms, or a group having an etheric oxygen atom at the end or between the carbon-carbon bonds of the perfluorohydrocarbon group. 11 , multiple R 12 and multiple R 13may be the same or different from each other, and are particularly preferably the same as each other. a1 is preferably 2 or 3, and particularly preferably 2.
[0018] Since the polymerization reactivity of monomer a is superior, R 11 , R 12 , R 13 is preferably a fluorine atom or a hydrogen atom, and R 11 , R 12 , R 13 It is more preferable that all of R are fluorine atoms or hydrogen atoms. From the viewpoint of heat resistance and chemical resistance of the cured product, 11 , R 12 , R 13 It is particularly preferable that all of are fluorine atoms. R 14 R may be linear, branched, or cyclic, preferably linear or branched, and particularly preferably linear. 14 The number of carbon atoms is preferably 2 to 10, more preferably 3 to 8, further preferably 3 to 6, and particularly preferably 3 to 5. R 14 may or may not have an ether type oxygen atom, but preferably has an ether type oxygen atom in terms of better crosslinking reactivity and rubber physical properties. R 14 The number of ether oxygen atoms in R is preferably 1 to 6, more preferably 1 to 3, and particularly preferably 1 or 2. 14 The etheric oxygen atom in R 14 It is preferred that the nucleotide sequence is located at the end of the nucleotide sequence.
[0019] Of the monomers represented by formula (1), specific examples of suitable monomers include those represented by formula (2) and those represented by formula (3).
[0020] (CF2=CF)2R 21 (2) In formula (2), R 21represents a divalent perfluoroalkylene group having 2 to 10 carbon atoms, or a group having an etheric oxygen atom at the terminal or between the carbon-carbon bonds of the perfluoroalkylene group.
[0021] Specific examples of the monomer represented by formula (2) include CF2=CFO(CF2)2OCF=CF2, CF2=CFO(CF2)3OCF=CF2, CF2=CFO(CF2)4OCF=CF2, and CF2=CFO(CF2)6OCF=CF 2、 CF2=CFO(CF2)8OCF=CF2, CF2=CFO(CF2)2OCF(CF3)CF2OCF=CF2, CF2=CFO(CF2)2O(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2O(CF2CF2O)2CF=CF2, CF Examples include 2=CFO(CF2O)3O(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2CF(CF3)O(CF2)2OCF(CF3)CF2OCF=CF2, and CF2=CFOCF2CF2O(CF2O)2CF2CF2OCF=CF2. Among the monomers represented by formula (2), specific examples of more suitable monomers include CF2=CFO(CF2)3OCF=CF2 (hereinafter also referred to as "C3DVE") and CF2=CFO(CF2)4OCF=CF2 (hereinafter also referred to as "C4DVE" or "PBDVE").
[0022] (CH2=CH)2R 31 (3) In formula (3), R 31 represents a divalent perfluoroalkylene group having 2 to 10 carbon atoms, or a group having an etheric oxygen atom at the terminal or between the carbon-carbon bonds of the perfluoroalkylene group.
[0023] Specific examples of the monomer represented by formula (3) include CH2=CH(CF2)2CH=CH2, CH2=CH(CF2)4CH=CH2, and CH2=CH(CF2)6CH=CH2. Among the monomers represented by formula (3), a more preferred specific example of the monomer is CH2=CH(CF2)6CH=CH2 (hereinafter, also referred to as "C6DV").
[0024] When the monomer a is copolymerized, the polymerizable double bond at the end of the monomer a reacts during the polymerization to give a fluorine-containing copolymer A1 having a branched chain.
[0025] The PAVE units are perfluoro(alkyl vinyl ether) based units. The PAVE is preferably a monomer represented by formula (4) from the viewpoint of excellent polymerization reactivity and rubber physical properties. CF2=CF-OR f4 (4) In formula (4), R f4 R represents a perfluoroalkyl group having 1 to 10 carbon atoms. f4 The number of carbon atoms in the alkyl group is preferably 1 to 8, more preferably 1 to 6, further preferably 1 to 5, and particularly preferably 1 to 3, from the viewpoint of superior polymerization reactivity. The perfluoroalkyl group may be linear or branched.
[0026] Specific examples of PAVE include perfluoro(methyl vinyl ether) (hereinafter also referred to as "PMVE"), perfluoro(ethyl vinyl ether) (hereinafter also referred to as "PEVE"), and perfluoro(propyl vinyl ether) (hereinafter also referred to as "PPVE"), and among these, PMVE and PPVE are preferred.
[0027] Equation (5) is as follows. CF2=CF-OR f5 (5) In formula (5), R f5 R represents a perfluoroalkyl group having 1 to 8 carbon atoms and containing 1 to 5 etheric oxygen atoms. f5 The carbon number of the group is preferably 1 to 6, and particularly preferably 1 to 5.
[0028] Specific examples of the monomer represented by formula (5) include perfluoro(3,6-dioxa-1-heptene), perfluoro(3,6-dioxa-1-octene), and perfluoro(5-methyl-3,6-dioxa-1-nonene).
[0029] As the monomer having another halogen atom, a monomer having at least one of an iodine atom and a bromine atom is preferable.Specific examples of such a monomer include CF2=CFBr, CH2=CHCF2CF2Br, CF2=CF-O-CF2CF2-I, CF2=CF-O-CF2CF2-Br, CF2=CF-O-CF2CF2CH2-I, CF2=CF-O-CF2CF2CH2-Br, CF2=CF-O-CF2CF2(CF3)-O-CF2CF2CH2-I, and CF2=CF-O-CF2CF2(CF3)-O-CF2CF2CH2-Br.
[0030] When the fluorine-containing copolymer A1 contains VdF units, the content thereof is preferably from 45 to 70 mol %, more preferably from 50 to 60 mol %, based on all units in the fluorine-containing copolymer A1. When the fluorine-containing copolymer A1 contains TFE units, the content thereof is preferably from 10 to 25 mol %, more preferably from 20 to 22 mol %, based on all units in the fluorine-containing copolymer A1. When the fluorine-containing copolymer A1 contains HFP units, the content thereof is preferably from 15 to 30 mol %, more preferably from 20 to 28 mol %, based on all units in the fluorine-containing copolymer A1. When the fluorine-containing copolymer A1 contains other monomer units, the content thereof is preferably from 0.1 to 5 mol %, more preferably from 0.1 to 3 mol %, based on all units of the fluorine-containing copolymer A1.
[0031] Preferred combinations of the units contained in the fluorine-containing copolymer A1 are shown below. Combination 1-1: Combination of VdF units, TFE units, and HFP units Combination 1-2: Combination of VdF unit and HFP unit
[0032] The copolymer composition in the combinations 1-1 and 1-2 preferably has the following molar ratio: When the molar ratio is as follows, the crosslinking reactivity of the copolymer is excellent, and further, the crosslinked product has better fuel permeation resistance and rubber properties in a low temperature environment. Combination 1-1: VdF unit / TFE unit / HFP unit=45-70 / 10-25 / 15-30 (molar ratio) Combination 1-2: VdF unit / HFP unit=70-80 / 20-30 (molar ratio)
[0033] The fluorine-containing copolymer A1 preferably has at least one of an iodine atom and a bromine atom. The iodine atom and the bromine atom react with an organic peroxide described later to become a crosslinking site when the fluorine-containing copolymer A1 is crosslinked. The iodine atom and the bromine atom have good reactivity, so that the crosslinking speed is fast. When the fluorine-containing copolymer A1 having an iodine atom and a bromine atom is crosslinked with an organic peroxide, the obtained crosslinked product has excellent chemical resistance. In addition, the adhesion between the first crosslinked layer and the second crosslinked layer can be improved. Examples of the iodine or bromine atom that the fluorine-containing copolymer A1 may have include an iodine or bromine atom derived from a chain transfer agent having at least one of an iodine atom and a bromine atom described below, and an iodine or bromine atom in a unit based on a monomer having at least one of an iodine atom and a bromine atom described above. Among these, an iodine or bromine atom derived from a chain transfer agent having at least one of an iodine atom and a bromine atom described below is preferred. When a chain transfer agent is used, at least one of an iodine atom and a bromine atom can be introduced into the terminal of the fluorine-containing copolymer (polymer chain). When a monomer having at least one of an iodine atom and a bromine atom is used, at least one of an iodine atom and a bromine atom can be introduced into the side chain of the fluorine-containing copolymer.
[0034] Of the iodine atom and the bromine atom, the fluorine-containing copolymer A1 preferably contains an iodine atom from the viewpoint of the crosslinking reactivity of the fluorine-containing copolymer A1.
[0035] When the fluorine-containing copolymer A1 has at least one of an iodine atom and a bromine atom, the total content of the iodine atom and the bromine atom is preferably 0.01 to 5.0 mass%, more preferably 0.05 to 2.0 mass%, particularly preferably 0.1 to 1.0 mass%, based on the total mass of the fluorine-containing copolymer A1. When the total content is within the above range, the crosslinking reactivity of the fluorine-containing copolymer A1 is improved, and the mechanical properties of the crosslinked product are excellent. In addition, the total content of iodine atoms and bromine atoms means the content of only one atom when only one atom is contained, and means the total content of each atom when both atoms are contained.
[0036] The crosslinked product of the fluorocopolymer A1 can be obtained, for example, by heating the above-mentioned fluorocopolymer A1 in the presence of a crosslinking agent or the like described later.
[0037] The content M of the crosslinked product of the fluorocopolymer A1 relative to the total of the crosslinked product of the fluorocopolymer A1 and the crosslinked product of the non-fluoropolymer A2 described below. CA is 85% by mass or more, and from the viewpoint of superior dimensional stability after use of the present laminate in a high-temperature environment, it is preferably 90% by mass or more, and more preferably 95% by mass or more. Here, the total of the crosslinked product of the fluorocopolymer A1 and the crosslinked product of the non-fluoropolymer A2 means the content of the crosslinked product of the fluorocopolymer A1 when the first crosslinked layer does not contain a crosslinked product of the non-fluoropolymer A2. M CA is preferably 100% by mass. In other words, the first crosslinked layer preferably does not contain a crosslinked product of the non-fluoropolymer A2. This provides better dimensional stability after the present laminate is used in a high-temperature environment.
[0038] The method for measuring the content of the crosslinked product of the fluorinated copolymer A1 and the content of the non-fluorinated polymer A2 in the first crosslinked layer is as described in the Examples section below.
[0039] The content of the crosslinked product of fluorocopolymer A1 is preferably 60 to 90 mass%, more preferably 64 to 90 mass%, and even more preferably 68 to 83 mass%, relative to the total mass of the first crosslinked layer, from the viewpoint of better dimensional stability after use of the present laminate in a high-temperature environment.
[0040] (Physical Properties of Fluorine-Containing Copolymer A1) The Tg of the fluorocopolymer A1 is preferably 15°C or lower, preferably from -30 to 15°C, more preferably from -20 to -5°C, in order that the rubber properties of the crosslinked product of the fluorocopolymer A1 can be fully exhibited.
[0041] (Production method of fluorine-containing copolymer A1) An example of the method for producing the fluorine-containing copolymer A1 is a method in which the above-mentioned monomers are polymerized in the presence of a chain transfer agent and a radical polymerization initiator.
[0042] Examples of the chain transfer agent include chain transfer agents having at least one of an iodine atom and a bromine atom, linear or cyclic alkanes such as methane, ethane, propane, butane, pentane, hexane, and cyclohexane, alcohols such as methanol, ethanol, and propanol, and mercaptans such as tert-dodecyl mercaptan, n-dodecyl mercaptan, and n-octadecyl mercaptan. Among these, from the viewpoint of the crosslinking reactivity of the fluorine-containing copolymer A1, chain transfer agents having at least one of an iodine atom and a bromine atom are preferred. The chain transfer agent may be used alone or in combination of two or more kinds.
[0043] Specific examples of the chain transfer agent having at least one of an iodine atom and a bromine atom include IR f6 -I (where R f6 represents a perfluoroalkylene group having 1 to 8 carbon atoms or a perfluorooxyalkylene group having 2 to 8 carbon atoms. f7 -Br(wherein, R f7 represents a perfluoroalkylene group having 1 to 8 carbon atoms or a perfluorooxyalkylene group having 2 to 8 carbon atoms.1 -I (where R 1 represents an alkylene group having 1 to 8 carbon atoms or an oxyalkylene group having 2 to 8 carbon atoms. IR f6 Specific examples of -I include diiodoperfluoromethane, 1,2-diiodoperfluoroethane, 1,3-diiodoperfluoropropane, 1,4-diiodoperfluorobutane, 1,5-diiodoperfluoropentane, 1,6-diiodoperfluorohexane, 1,7-diiodoperfluoroheptane, and 1,8-diiodoperfluorooctane. Among them, 1,4-diiodoperfluorobutane and 1,6-diiodoperfluorohexane are preferred, and 1,4-diiodoperfluorobutane is particularly preferred. IR f7 Specific examples of -Br include 1-iodo-4-bromoperfluorobutane, 1-iodo-6-bromoperfluorohexane, and 1-iodo-8-bromoperfluorooctane. Among them, 1-iodo-4-bromoperfluorobutane and 1-iodo-6-bromoperfluorohexane are preferred, and 1-iodo-4-bromoperfluorobutane is particularly preferred. IR 1 Specific examples of -I include 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, and 1,8-diiodooctane. When the above monomers are polymerized in the presence of a chain transfer agent having at least one of an iodine atom and a bromine atom, iodine atoms and / or bromine atoms can be introduced into the fluorine-containing copolymer.
[0044] When a chain transfer agent having at least one of an iodine atom and a bromine atom is used, the amount of the agent is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 17 parts by mass, and particularly preferably 2 to 15 parts by mass, relative to 100 parts by mass of the total amount of monomers used in the polymerization of the fluorocopolymer A1. If the amount is 0.1 part by mass or more, the polymerization time can be shortened. On the other hand, if the amount is 20 parts by mass or less, the rubber properties of the crosslinked product of the fluorocopolymer A1 are good.
[0045] The polymerization temperature is appropriately selected depending on the monomer composition, the decomposition temperature of the radical polymerization initiator, etc. The polymerization temperature is preferably 0 to 60°C, more preferably 10 to 50°C, and particularly preferably 20 to 40°C.
[0046] For details of the components other than those mentioned above used in the production of the fluorine-containing copolymer A1 and the production method, reference can be made to the examples of Japanese Patent No. 4,089,923 and the methods described in Japanese Patent Nos. 3,860,114 and 5,744,902.
[0047] <Non-fluorinated polymer A2> The non-fluorinated polymer A2 is a polymer containing no fluorine atoms, and preferably exhibits rubber properties through crosslinking, that is, the crosslinked product of the non-fluorinated polymer A2 preferably exhibits rubber properties. Specific examples of the non-fluorinated polymer A2 include (meth)acrylic acid ester polymers, ethylene-(meth)acrylic acid ester copolymers, silicone polymers, ethylene-propylene-diene copolymers, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, chloroprene polymers, isobutylene-isoprene copolymers, isoprene polymers, butadiene polymers, chlorinated polyethylene, chlorosulfonated polyethylene, acrylonitrile-butadiene rubber, and hydrogenated acrylonitrile-butadiene rubber. Among these, ethylene-(meth)acrylic acid ester copolymers and ethylene-propylene-diene copolymers are preferred from the standpoints of heat resistance, availability, and economy.
[0048] The crosslinked product of the non-fluorinated polymer A2 can be obtained, for example, by heating the above-mentioned non-fluorinated polymer A2 in the presence of a crosslinking agent or the like described later. Here, since the crosslinked product of the non-fluoropolymer A2 is an optional component, the first crosslinked layer may or may not contain the crosslinked product of the non-fluoropolymer A2. When it is desired to facilitate processing or improve low temperature resistance, the crosslinked product of the non-fluoropolymer A2 may be added to the first crosslinked layer. It is preferable that the laminate having the first crosslinked layer containing the crosslinked product of the non-fluoropolymer A2 is used in an environment of less than 150°C. In addition, it is preferable that the laminate having the first crosslinked layer containing the crosslinked product of the non-fluoropolymer A2 is used so that the first crosslinked layer does not come into contact with a chemical solution. The content of the crosslinked product of the non-fluoropolymer A2 is preferably 11 mass% or less, more preferably 7 mass% or less, and even more preferably 0 mass% (i.e., the first crosslinked layer does not contain any crosslinked product of the non-fluoropolymer A2), relative to the total mass of the first crosslinked layer, in order to provide better dimensional stability after use of this laminate in a high-temperature environment.
[0049] The Tg of the non-fluorinated polymer A2 is preferably 15°C or lower, preferably from -50 to 15°C, more preferably from -30 to 10°C, in order that the rubber properties of the crosslinked product of the non-fluorinated polymer A2 can be fully exhibited.
[0050] <Other ingredients> The first crosslinked layer may contain components other than the crosslinked product of the fluorine-containing copolymer A1 and the crosslinked product of the non-fluorine-containing polymer A2. Specific examples of such components include an uncrosslinked product of the fluorine-containing copolymer A1 (i.e., the above-mentioned fluorine-containing copolymer A1), an uncrosslinked product of the non-fluorine-containing polymer A2 (i.e., the above-mentioned non-fluorine-containing polymer A2), an unreacted crosslinking agent, a sintered body of diatomaceous earth, and silica. Specific examples of other components other than those mentioned above include unreacted crosslinking aids (e.g., triallyl cyanurate, triallyl isocyanurate, trimethallyl isocyanurate), unreacted acid acceptors (e.g., fatty acid esters, fatty acid metal salts, oxides of divalent metals (magnesium oxide, calcium oxide, zinc oxide, lead oxide, etc.)), fillers (e.g., carbon black, barium sulfate, calcium metasilicate, calcium carbonate, titanium oxide, silicon dioxide, clay, talc), scorch retarders (e.g., phenolic hydroxyl group-containing compounds such as o-phenylphenol and bisphenol A, quinones such as hydroquinone, α-methylstyrene dimers such as 2,4-di(3-isopropylphenyl)-4-methyl-1-pentene), crown ethers (e.g., 18-crown-6), plasticizers (e.g., adipic acid ether ester compounds), and processing aids (e.g., oleic acid glyceride).
[0051] When the first crosslinked layer contains other components, the content of the other components is preferably 20 to 32 mass %, more preferably 20 to 31 mass %, and even more preferably 20 to 30 mass %, based on the total mass of the first crosslinked layer.
[0052] (Crosslinking agent) Specific examples of the crosslinking agent include organic peroxides and amine-based crosslinking agents, with organic peroxides being preferred since the resulting crosslinked product has excellent chemical resistance. Specific examples of organic peroxides include dialkyl peroxides, α,α'-bis(tert-butylperoxy)-p-diisopropylbenzene, α,α'-bis(tert-butylperoxy)-m-diisopropylbenzene, benzoyl peroxide, tert-butylperoxybenzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylcumyl peroxide, dicumyl peroxide, and bis-2,4-dichlorobenzoyl peroxide. Specific examples of dialkyl peroxides include 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroxyperoxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne, tert-butylperoxymaleic acid, and tert-butylperoxyisopropyl carbonate. Specific examples of amine-based crosslinking agents include aliphatic polyamines such as ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and hexamethylenetetramine; aromatic polyamines such as p-phenylenediamine, cumenediamine, and N,N'-dicinnamylidene-1,6-hexanediamine; and amine carbamates such as ethylenediamine carbamate and hexamethylenediamine carbamate.
[0053] (Sintered diatomaceous earth) The first crosslinked layer preferably contains a sintered body of diatomaceous earth, since this can further improve the adhesion between the first crosslinked layer and the second crosslinked layer.
[0054] Sintered diatomaceous earth can be obtained by firing diatomaceous earth, which is a soft rock or soil mainly composed of diatom shells and contains silica as a main component, as well as alumina and iron oxide. The sintered body of diatomaceous earth is preferably Celite (registered trademark), which is a sintered body obtained by firing diatomaceous earth in the presence of a carbonate such as sodium carbonate. Specific examples of sintered diatomaceous earth include Celite 350, Celite 505, Celite 512, Celite 577, and Standard Super-Cel (all manufactured by Celite Corporation).
[0055] When the first crosslinked layer contains a sintered body of diatomaceous earth, the content of the sintered body of diatomaceous earth per 100 parts by mass of the crosslinked product of fluorocopolymer A1 is preferably 1 to 10 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 5 to 10 parts by mass, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. When the first crosslinked layer contains a diatomaceous earth sintered body, the content of the diatomaceous earth sintered body is preferably 1 to 10 mass %, more preferably 2 to 9 mass %, and even more preferably 3 to 8 mass %, relative to the total mass of the first crosslinked layer.
[0056] (silica) The first crosslinked layer preferably contains silica, since this can further improve the adhesion between the first crosslinked layer and the second crosslinked layer. As the silica, either hydrophobic silica or hydrophilic silica may be used, but hydrophilic silica is preferred from the viewpoints of further improving the adhesion between the first crosslinked layer and the second crosslinked layer and suppressing the deterioration of the rubber properties of the crosslinked product of the fluorocopolymer. Here, hydrophobic silica means silica that has been subjected to a hydrophobic treatment using hexamethyldisilazane, silicone oil, or the like. Moreover, the hydrophilic silica is silica that has not been subjected to the above-mentioned hydrophobic treatment, and specifically means silica having hydrophilic groups such as silanol groups on its surface.
[0057] The specific surface area of silica (especially hydrophilic silica) by the BET method is set to 20 m2 in order to further improve the adhesion between the first crosslinked layer and the second crosslinked layer. 2 / g or more is preferable, and 30 to 1000m 2 / g is more preferable, and 70 to 500m 2 / g is more preferable, and 100 to 450m 2 / g is particularly preferable, and more preferably, 150 to 400 m 2 / g or less is preferable, and 175 to 350m 2 / g is more preferred.
[0058] The apparent specific gravity of silica (particularly hydrophilic silica) is preferably 20 to 300 g / L, more preferably 30 to 250 g / L, and even more preferably 40 to 200 g / L, from the viewpoint of further improving the adhesion between the first crosslinked layer and the second crosslinked layer. When the apparent specific gravity is within the above range, the decrease in elongation of the crosslinked product of the fluorocopolymer is suppressed, and good hardness is obtained.
[0059] The average primary particle size of the silica is preferably 5 to 50 nm, more preferably 6 to 45 nm, and even more preferably 7 to 40 nm, from the viewpoint of further improving the adhesion between the first crosslinked layer and the second crosslinked layer. When the average primary particle size of the silica is within the above range, the silica is excellent in uniform dispersibility in the second crosslinked layer. Silica is available as a commercial product, and examples thereof include hydrophilic silica such as AEROSIL 50, 200, and 300 (all manufactured by Nippon Aerosil Co., Ltd.). The silica may be used alone or in combination of two or more kinds.
[0060] When the first crosslinked layer contains silica, the content of silica is preferably 1 to 10 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 5 to 10 parts by mass, relative to 100 parts by mass of the crosslinked product of fluorocopolymer A1, from the viewpoint of further improving the adhesion between the first crosslinked layer and the second crosslinked layer. When the first crosslinked layer contains silica, the content of silica is preferably 1 to 10 mass%, more preferably 2 to 9 mass%, and even more preferably 3 to 8 mass%, relative to the total mass of the first crosslinked layer, in order to further improve the adhesion between the first crosslinked layer and the second crosslinked layer.
[0061] The first crosslinked layer preferably contains both sintered diatomaceous earth and silica. This provides particularly excellent adhesion between the first crosslinked layer and the second crosslinked layer. Although the details of the reason for this are not clear, it is presumed that hydrogen bonds between hydroxyl groups contained in the sintered diatomaceous earth and silica and hydrogen atoms in the fluorine-containing polymer and non-fluorine-containing polymer, as well as other intermolecular interactions, are involved. When the first crosslinked layer contains diatomaceous earth sintered body and silica, the content ratio of the diatomaceous earth sintered body and silica (diatomaceous earth sintered body / silica) is preferably 1-10 / 1-10, more preferably 2-10 / 2-10, and even more preferably 5-10 / 5-10, in terms of better adhesion between the first crosslinked layer and the second crosslinked layer.
[0062] [Second crosslinked layer] The second crosslinked layer is disposed on the first crosslinked layer, and is preferably disposed so as to be in contact with the first crosslinked layer. The second crosslinked layer contains a crosslinked product of a fluorine-containing copolymer B1, and optionally contains a crosslinked product of a non-fluorine-containing polymer B2.
[0063] <Fluorine-containing copolymer B1> The fluorine-containing copolymer B1 is a copolymer having fluorine atoms and containing units based on two or more types of monomers, and exhibits rubber properties through crosslinking, i.e., the crosslinked product of the fluorine-containing copolymer B1 exhibits rubber properties. The combination of units based on monomers constituting the fluorine-containing copolymer B1 is different from the combination of units based on monomers constituting the fluorine-containing copolymer A1.
[0064] The fluorocopolymer B1 preferably has TFE units and propylene units because it has excellent resistance to basic compounds described below.
[0065] The fluorine-containing copolymer B1 may have units based on monomers other than those mentioned above (hereinafter also referred to as "other monomers"). Specific examples of the other monomers include monomer a, VdF, HFP, CTFE, PAVE, the monomer represented by the above formula (5), and ethylene. In addition, monomers other than those mentioned above that have other halogen atoms may also be mentioned. Specific examples of these other monomers are the same as the monomers described in the section on the first crosslinked layer, and preferred embodiments are also the same.
[0066] The fluorine-containing copolymer B1 may contain VdF units, but preferably does not substantially contain VdF units in order that the second crosslinked layer will have excellent chemical resistance (particularly, amine resistance). Here, "substantially free of VdF units" means that the content of VdF units is 0.1 mol % or less, preferably 0 mol %, based on all units of the fluorine-containing copolymer B1.
[0067] When the fluorine-containing copolymer B1 contains a TFE unit, the content thereof is preferably from 30 to 70 mol %, more preferably from 40 to 60 mol %, based on the total units of the fluorine-containing copolymer B1. When the fluorine-containing copolymer B1 contains a propylene unit, the content thereof is preferably from 30 to 70 mol %, more preferably from 40 to 60 mol %, based on the total units of the fluorine-containing copolymer B1. When the fluorine-containing copolymer B1 contains other monomer units, the content thereof is preferably from 0.01 to 10 mol %, more preferably from 0.05 to 5 mol %, based on all units of the fluorine-containing copolymer B1.
[0068] Preferred combinations of the units contained in the fluorine-containing copolymer B1 are shown below. Combination 2-1: Combination of TFE units and propylene units
[0069] The copolymer composition in combination 2-1 preferably has the following molar ratio: With the following molar ratio, the crosslinking reactivity of the copolymer is further improved, and the cured product is excellent in mechanical properties, heat resistance, chemical resistance, oil resistance, weather resistance, etc. Combination 1: TFE unit / propylene unit=40-60 / 40-60 (molar ratio)
[0070] The fluorine-containing copolymer B1 may have at least one of an iodine atom and a bromine atom, which serves as a crosslinking site when the fluorine-containing copolymer B1 is crosslinked. Specific examples of the iodine atom or bromine atom that the fluorine-containing copolymer B1 may have are the same as those described in the section regarding the first crosslinked layer, and preferred embodiments are also the same.
[0071] When the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom, the total content of the iodine atom and the bromine atom is preferably 0.01 to 5.0 mass%, more preferably 0.05 to 2.0 mass%, particularly preferably 0.1 to 1.0 mass%, based on the total mass of the fluorine-containing copolymer B1. When the total content is within the above range, the crosslinking reactivity of the fluorine-containing copolymer B1 is improved, and the mechanical properties of the crosslinked product are excellent. In addition, the total content of iodine atoms and bromine atoms means the content of only one atom when only one atom is contained, and means the total content of each atom when both atoms are contained.
[0072] In order to obtain better adhesion between the first crosslinked layer and the second crosslinked layer, it is preferable that at least one of the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom, and it is more preferable that both the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 have at least one of an iodine atom and a bromine atom.
[0073] The crosslinked product of the fluorocopolymer B1 can be obtained, for example, by heating the above-mentioned fluorocopolymer B1 in the presence of a crosslinking agent or the like described later.
[0074] The content M of the crosslinked product of the fluorine-containing copolymer B1 relative to the total of the crosslinked product of the fluorine-containing copolymer B1 and the crosslinked product of the non-fluorine-containing polymer B2 described below. CB is 85% by mass or more, and from the viewpoint of superior dimensional stability after use of the present laminate in a high-temperature environment, it is preferably 90% by mass or more, and more preferably 95% by mass or more. Here, the total of the crosslinked product of the fluorocopolymer B1 and the crosslinked product of the non-fluoropolymer B2 means the content of the crosslinked product of the fluorocopolymer B1 when the second crosslinked layer does not contain a crosslinked product of the non-fluoropolymer B2. M CB is preferably 100% by mass. In other words, the second crosslinked layer preferably does not contain a crosslinked product of the non-fluoropolymer B2. This provides better dimensional stability after the laminate is used in a high-temperature environment.
[0075] The method for measuring the content of the crosslinked product of the fluorinated copolymer B1 and the content of the non-fluorinated polymer B2 in the second crosslinked layer is as described in the Examples section below.
[0076] The above M CA and the above M CB The absolute value of the difference from is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of suppressing the occurrence of warping after storage of the present laminate in a high-temperature environment.
[0077] The content of the crosslinked product of fluorocopolymer B1 is preferably 60 to 90 mass%, more preferably 65 to 90 mass%, and even more preferably 70 to 83 mass%, relative to the total mass of the second crosslinked layer, from the viewpoint of better dimensional stability after use of the present laminate in a high-temperature environment.
[0078] (Physical properties of fluorine-containing copolymer B1) The Tg of the fluorocopolymer B1 is preferably 15° C. or lower, preferably from −30 to 15° C. or lower, more preferably from −20 to 10° C. or lower, in order that the rubber properties of the crosslinked product of the fluorocopolymer B1 may be fully exhibited.
[0079] (Production method of fluorine-containing copolymer B1) An example of the method for producing the fluorine-containing copolymer B1 includes a method in which the above-mentioned monomers are polymerized in the presence of a chain transfer agent and a radical polymerization initiator. The method for producing fluorocopolymer B1 is the same as the method for producing fluorocopolymer A1 described above, except that the combination of monomers used is different from the combination of monomers used in the method for producing fluorocopolymer A1, and the preferred embodiments are also the same.
[0080] <Non-fluorinated polymer B2> The non-fluorinated polymer B2 is a polymer containing no fluorine atoms, and preferably exhibits rubber properties through crosslinking, that is, the crosslinked product of the non-fluorinated polymer B2 preferably exhibits rubber properties. Specific examples of the non-fluorinated polymer B2 are the same as the specific examples of the non-fluorinated polymer A2, and preferred embodiments are also the same.
[0081] The crosslinked product of the non-fluorinated polymer B2 can be obtained, for example, by heating the above-mentioned non-fluorinated polymer B2 in the presence of a crosslinking agent or the like described later. Here, since the crosslinked product of the non-fluorinated polymer B2 is an optional component, the second crosslinked layer may or may not contain the crosslinked product of the non-fluorinated polymer B2. The content of the crosslinked non-fluoropolymer B2 is preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 0 mass% (i.e., the second crosslinked layer does not contain any crosslinked non-fluoropolymer B2) relative to the total mass of the second crosslinked layer, in order to provide better dimensional stability after use of this laminate in a high-temperature environment.
[0082] The Tg of the non-fluorinated polymer B2 is preferably 15° C. or lower, preferably −50 to 15° C., more preferably −30 to 10° C., in order that the rubber properties of the crosslinked product of the non-fluorinated polymer B2 can be fully exhibited.
[0083] <Other ingredients> The second crosslinked layer may contain components other than the crosslinked product of the fluorine-containing copolymer B1 and the crosslinked product of the non-fluorine-containing polymer B2. Specific examples of such components include an uncrosslinked product of the fluorine-containing copolymer B1 (i.e., the above-mentioned fluorine-containing copolymer B1), an uncrosslinked product of the non-fluorine-containing polymer B2 (i.e., the above-mentioned non-fluorine-containing polymer B2), an unreacted crosslinking agent, a sintered body of diatomaceous earth, and silica. Specific examples of the crosslinking agent, the sintered body of diatomaceous earth, and silica are the same as those of the crosslinking agent, the sintered body of diatomaceous earth, and silica described in the section of the first crosslinked layer, and preferred embodiments are also the same. Moreover, specific examples of other components than those mentioned above are similar to those described in the section on the first crosslinked layer, and therefore description thereof will be omitted.
[0084] When the second crosslinked layer contains other components, the content of the other components is preferably 15 to 40 mass %, more preferably 18 to 30 mass %, and even more preferably 19 to 29 mass %, based on the total mass of the second crosslinked layer.
[0085] When the second crosslinked layer contains a diatomaceous earth sintered body, the content of the diatomaceous earth sintered body is preferably 1 to 15 parts by mass, more preferably 3 to 15 parts by mass, and even more preferably 5 to 15 parts by mass, per 100 parts by mass of the crosslinked product of fluorocopolymer B1, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. When the second crosslinked layer contains a sintered diatomaceous earth, the content of the sintered diatomaceous earth relative to the total mass of the second crosslinked layer is preferably 1 to 13 mass%, more preferably 2 to 12 mass%, and even more preferably 4 to 11 mass%.
[0086] When the second crosslinked layer contains silica, the content of silica is preferably 1 to 15 parts by mass, more preferably 3 to 15 parts by mass, and even more preferably 5 to 15 parts by mass, per 100 parts by mass of the crosslinked product of fluorine-containing copolymer B1, from the viewpoint of further improving the adhesion between the first crosslinked layer and the second crosslinked layer. When the second crosslinked layer contains silica, the content of silica is preferably 1 to 10 mass%, more preferably 3 to 10 mass%, and even more preferably 5 to 9 mass%, relative to the total mass of the second crosslinked layer, in order to further improve the adhesion between the first crosslinked layer and the second crosslinked layer.
[0087] The second cross-linked layer preferably contains both sintered diatomaceous earth and silica, which provides particularly excellent adhesion between the first cross-linked layer and the second cross-linked layer for the same reasons as in the case where the first cross-linked layer contains sintered diatomaceous earth and silica. When the second crosslinked layer contains diatomaceous earth sintered body and silica, the content ratio of the diatomaceous earth sintered body and silica (diatomaceous earth sintered body / silica) is preferably 1-15 / 1-15, more preferably 3-15 / 3-15, and even more preferably 5-15 / 5-15, in terms of better adhesion between the first crosslinked layer and the second crosslinked layer.
[0088] In order to obtain better adhesion between the first crosslinked layer and the second crosslinked layer, it is preferable that at least the first crosslinked layer contains both a sintered body of diatomaceous earth and silica, and that the fluorine-containing copolymer B1 in the second crosslinked layer has at least one of an iodine atom and a bromine atom.
[0089] [Application] The laminate can be used as, for example, a hose, a sealing material, a valve, a roll, a covering material, etc. The laminate can be used in the form of, for example, a cylinder, a sheet, an O-ring, a V-ring, etc.
[0090] The use of the present laminate is not particularly limited, but it is preferable to use it as a member that comes into contact with a basic compound. Examples of basic compounds include organic bases and inorganic bases. Examples of organic bases include amines. Examples of amines include ammonia, ethylenediamine, and tetraalkylammonium hydroxide. Examples of tetraalkylammonium hydroxides include tetramethylammonium hydroxide. Examples of inorganic bases include alkali metal hydroxides. Examples of alkali metal hydroxides include sodium hydroxide and potassium hydroxide. The laminate is particularly suitable for use as a member that comes into contact with ammonia. "Comes into contact with ammonia" includes, for example, contact with 100% ammonia liquid and aqueous ammonia solution, and contact with ammonia generated by a reaction such as decomposition of a compound. An example of a compound that generates ammonia by a reaction such as decomposition is urea. Ammonia is sometimes used to treat nitrogen oxides in fuels and exhaust gases. Urea is sometimes used as a source of ammonia because it generates ammonia through hydrolysis. Examples of components that come into contact with basic compounds include hoses, seals, valves, and the like used in facilities for storing, transporting, reacting, or measuring basic compounds, engines and power generating devices that use basic compounds (particularly, ammonia and urea) as raw materials, and devices that treat exhaust gases containing nitrogen oxides. When the laminate is used as a member that contacts with a basic compound, it is preferable that the second crosslinked layer is arranged so as to contact with the basic compound.In particular, if the crosslinked product of the fluorine-containing copolymer B1 contained in the second crosslinked layer is a crosslinked product of the fluorine-containing copolymer having TFE unit and propylene unit, it is more excellent in resistance to basic compounds, and is therefore preferably used as a member that contacts with basic compounds.
[0091] The laminate is also preferably used as a member that comes into contact with fuel. "Comes into contact with fuel" includes contact with liquid fuel and gaseous fuel. Liquid fuel also includes atomized fuel. Examples of members that come into contact with fuel (e.g., diesel, gasoline, natural gas, etc.) include hoses, sheets, O-rings, gaskets, etc. used in fuel storage facilities and transportation equipment that uses fuel. Specific examples of members that come into contact with fuel include turbocharger hoses, oil return hoses, exhaust gas hoses, EGR hoses, oil hoses, and fuel hoses. When the present laminate is used in a member that comes into contact with fuel, it is preferable that the second cross-linked layer is disposed so as to come into contact with the fuel.
[0092] [Method for producing laminate] The method for producing the laminate is not particularly limited, but for example, a method of heating a precursor laminate (described later) in which a second composition layer (described later) containing a fluorine-containing copolymer B1, a crosslinking agent, and optionally a non-fluorine polymer B2 is disposed on a first composition layer (described later) containing a fluorine-containing copolymer A1, a crosslinking agent, and optionally a non-fluorine polymer A2 is disposed. As a result, the fluorine-containing copolymer A1 and the optionally contained non-fluorine polymer A2 in the first composition layer are crosslinked to form the first crosslinked layer, and the fluorine-containing copolymer B1 and the optionally contained non-fluorine polymer B2 in the second composition layer are crosslinked to form the second crosslinked layer, thereby obtaining the laminate having the first crosslinked layer and the second crosslinked layer disposed on the first crosslinked layer.
[0093] The laminate may have a first crosslinked layer, a second crosslinked layer disposed on the first crosslinked layer, and other layers. Examples of the main components of the other layers include fluorine-containing polymers, non-fluorine-containing polymers, metals, glass, and carbon. The main components of the other layers may be in the form of a plate, fiber, fabric, or nonwoven fabric. Examples of the present laminate having other layers include a laminate having a first crosslinked layer, a second crosslinked layer disposed on the first crosslinked layer, and another layer disposed on the second crosslinked layer, and a laminate having another layer, a first crosslinked layer disposed on the other layer, and a second crosslinked layer disposed on the first crosslinked layer. The laminate may have a plurality of other layers, but the first crosslinked layer is disposed so as to be in contact with the second crosslinked layer.
[0094] Specific examples of the method for crosslinking each polymer by heating include heat press crosslinking, steam crosslinking, hot air crosslinking, oil bath crosslinking, and salt bath crosslinking. The heating temperature is preferably 130 to 180° C., more preferably 140 to 170° C. When heating, the temperature may be increased or decreased stepwise. The heating time is preferably from 10 minutes to 3 hours. When hot press crosslinking is carried out, the pressure is preferably 5 to 30 MPa.
[0095] The thicknesses of the first crosslinked layer and the second crosslinked layer in the laminate of the present invention are not particularly limited. For example, when the laminate of the present invention is used as a hose, the thickness of each of the first crosslinked layer and the second crosslinked layer can be 0.1 to 200 mm, more preferably 0.1 to 150 mm, and particularly preferably 0.1 to 100 mm. For example, when the laminate of the present invention is used as a sealing material, the thickness of each of the first crosslinked layer and the second crosslinked layer can be 10 to 300 mm, more preferably 10 to 200 mm, and particularly preferably 10 to 100 mm. For example, when the laminate of the present invention is used as a roll, the thickness of each of the first crosslinked layer and the second crosslinked layer can be 10 to 5000 mm, more preferably 10 to 3000 mm, and particularly preferably 10 to 2000 mm.
[0096] [Precursor laminate] A laminate having a first composition layer and a second composition layer disposed on the first composition layer is called a precursor laminate. The above-mentioned present laminate can be obtained by crosslinking the fluorine-containing copolymer contained in the precursor laminate of the present invention (hereinafter also referred to as the present precursor laminate). The present precursor laminate has a first composition layer and a second composition layer disposed on the first composition layer, wherein the first composition layer comprises a fluorinated copolymer A1 and a crosslinking agent, and optionally comprises a non-fluorinated polymer A2, and the second composition layer comprises a fluorinated copolymer B1 and a crosslinking agent, and optionally comprises a non-fluorinated polymer B2. In addition, in this precursor laminate, the combination of units based on monomers constituting the fluorocopolymer A1 is different from the combination of units based on monomers constituting the fluorocopolymer B1. In the present laminate, the content M of the fluorocopolymer A1 relative to the total of the fluorocopolymer A1 and the non-fluoropolymer A2 is PA is 85% by mass or more, and the content M of the fluorine-containing copolymer B1 relative to the total of the fluorine-containing copolymer B1 and the non-fluorine-containing polymer B2 is PB is 85 mass % or more.
[0097] [First composition layer] The first composition layer contains a fluorinated copolymer A1 and a crosslinking agent, and optionally contains a non-fluorinated polymer A2. Details of the fluorinated copolymer A1, the crosslinking agent, and the non-fluorinated polymer A2 are as described in the section on the first crosslinked layer, and therefore description thereof will be omitted. The first composition layer may contain components other than the fluorinated copolymer A1, the crosslinking agent, and the non-fluorinated polymer A2. Details of the other components are as described in the section on the first crosslinked layer, and therefore description thereof will be omitted.
[0098] The content M of the fluorine-containing copolymer A1 relative to the total of the fluorine-containing copolymer A1 and the non-fluorine-containing polymer A2 PAis 85% by mass or more, and from the viewpoint of superior dimensional stability after use of the present laminate in a high-temperature environment, it is preferably 90% by mass or more, and more preferably 95% by mass or more. Here, the total of the fluorine-containing copolymer A1 and the non-fluorine-containing polymer A2 means the content of the crosslinked product of the fluorine-containing copolymer A1 when the first composition layer does not contain the non-fluorine-containing polymer A2. M PA is preferably 100% by mass. In other words, the first composition layer preferably does not contain the non-fluoropolymer A2. This provides better dimensional stability after the present laminate is used in a high-temperature environment.
[0099] The content of the fluorocopolymer A1 is preferably 60 to 90 mass%, more preferably 64 to 90 mass%, and even more preferably 68 to 83 mass%, relative to the total mass of the first composition layer, since the present laminate has better dimensional stability after use in a high-temperature environment.
[0100] The content of the crosslinking agent is preferably 0.1 to 5.0 parts by mass, more preferably 0.5 to 4.0 parts by mass, and even more preferably 1.0 to 3.0 parts by mass, per 100 parts by mass of fluorocopolymer A1, from the viewpoint of sufficient crosslinking of fluorocopolymer A1. The content of the crosslinking agent is preferably 0.1 to 1.5 mass %, more preferably 0.3 to 1.2 mass %, and even more preferably 0.5 to 1.0 mass %, relative to the total mass of the first composition layer, from the viewpoint of sufficient crosslinking of the fluorocopolymer A1.
[0101] The content of the other components is preferably from 20 to 32 mass %, more preferably from 20 to 31 mass %, and even more preferably from 20 to 30 mass %, based on the total mass of the first composition layer.
[0102] The first composition layer preferably contains at least one of a sintered body of diatomaceous earth and silica, and more preferably contains both, among other components, which can further improve the adhesion between the first crosslinked layer and the second crosslinked layer.
[0103] The content of the sintered diatomaceous earth per 100 parts by mass of fluorocopolymer A1 is preferably 1 to 10 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 5 to 10 parts by mass, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. The content of the diatomaceous earth sintered body is preferably from 1 to 10 mass %, more preferably from 2 to 9 mass %, and even more preferably from 3 to 8 mass %, based on the total mass of the first composition layer.
[0104] The content of silica is preferably 1 to 10 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 5 to 10 parts by mass, per 100 parts by mass of fluorocopolymer A1, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. The content of silica is preferably 1 to 10 mass%, more preferably 2 to 9 mass%, and even more preferably 3 to 8 mass%, relative to the total mass of the first composition layer, in order to achieve better adhesion between the first crosslinked layer and the second crosslinked layer.
[0105] The content of each component in the first composition layer is calculated based on the amount of each component contained in the first composition described below.
[0106] [Second composition layer] The second composition layer contains a fluorine-containing copolymer B1 and a crosslinking agent, and optionally contains a non-fluorine-containing polymer B2. Details of the fluorine-containing copolymer B1, the crosslinking agent, and the non-fluorine-containing polymer B2 are as described in the section on the second crosslinked layer, and therefore description thereof will be omitted. The second composition layer may contain other components in addition to the fluorinated copolymer B1, the crosslinking agent, and the non-fluorinated polymer B2. Details of the other components are as described in the section on the second crosslinked layer, and therefore description thereof will be omitted.
[0107] The content M of the fluorine-containing copolymer B1 relative to the total of the fluorine-containing copolymer B1 and the non-fluorine-containing polymer B2 PB is 85% by mass or more, and from the viewpoint of superior dimensional stability after use of the present laminate in a high-temperature environment, it is preferably 90% by mass or more, and more preferably 95% by mass or more. Here, the total of the fluorine-containing copolymer B1 and the non-fluorine-containing polymer B2 means the content of the crosslinked product of the fluorine-containing copolymer B1 when the second composition layer does not contain the non-fluorine-containing polymer B2. M PB is preferably 100% by mass. In other words, the second composition layer preferably does not contain the non-fluoropolymer B2. This provides better dimensional stability after the present laminate is used in a high-temperature environment.
[0108] The content of the fluorocopolymer B1 is preferably 60 to 90 mass%, more preferably 65 to 90 mass%, and even more preferably 70 to 83 mass%, based on the total mass of the second composition layer, since the laminate has better dimensional stability after use in a high-temperature environment.
[0109] The content of the crosslinking agent is preferably 0.1 to 5.0 parts by mass, more preferably 0.5 to 4.0 parts by mass, and even more preferably 1.0 to 3.0 parts by mass, per 100 parts by mass of the fluorocopolymer B1, from the viewpoint of sufficient crosslinking of the fluorocopolymer B1. The content of the crosslinking agent is preferably 0.1 to 1.5 mass %, more preferably 0.3 to 1.3 mass %, and even more preferably 0.5 to 1.2 mass %, relative to the total mass of the second composition layer, from the viewpoint of sufficient crosslinking of the fluorocopolymer B1.
[0110] The content of the other components is preferably from 15 to 40 mass %, more preferably from 18 to 30 mass %, and even more preferably from 19 to 29 mass %, based on the total mass of the second composition layer.
[0111] The second composition layer preferably contains at least one of a sintered body of diatomaceous earth and silica, and more preferably contains both, among other components, which can further improve the adhesion between the first crosslinked layer and the second crosslinked layer.
[0112] The content of the sintered diatomaceous earth per 100 parts by mass of fluorocopolymer B1 is preferably 1 to 15 parts by mass, more preferably 3 to 15 parts by mass, and even more preferably 5 to 15 parts by mass, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. The content of the diatomaceous earth sintered body is preferably from 1 to 13 mass %, more preferably from 2 to 12 mass %, and even more preferably from 4 to 11 mass %, based on the total mass of the second composition layer.
[0113] The content of silica is preferably 1 to 15 parts by mass, more preferably 3 to 15 parts by mass, and even more preferably 5 to 15 parts by mass, per 100 parts by mass of fluorine-containing copolymer B1, from the viewpoint of better adhesion between the first crosslinked layer and the second crosslinked layer. The content of silica is preferably 1 to 10 mass%, more preferably 3 to 10 mass%, and even more preferably 5 to 9 mass%, relative to the total mass of the second composition layer, in order to achieve better adhesion between the first crosslinked layer and the second crosslinked layer.
[0114] The content of each component in the second composition layer is calculated based on the amount of each component contained in the second composition described below.
[0115] The above M PA and the above M PB The absolute value of the difference from is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 0% by mass, in order to prevent warping of the present laminate after storage in a high-temperature environment.
[0116] In order to obtain better adhesion between the first crosslinked layer and the second crosslinked layer, it is preferred that at least the first composition layer contains both a sintered body of diatomaceous earth and silica, and that the fluorine-containing copolymer B1 in the second composition layer has at least one of an iodine atom and a bromine atom.
[0117] [Method for producing precursor laminate] The method for producing the precursor laminate is not particularly limited, but examples include a method in which a first composition containing a fluorocopolymer A1, a crosslinking agent, and optionally a non-fluoropolymer A2, and a second composition containing a fluorocopolymer B1, a crosslinking agent, and optionally a non-fluoropolymer B2 are each formed into a sheet, and a second composition layer obtained using the second composition is laminated on the first composition layer obtained using the first composition. Another example of a method for producing the precursor laminate includes a method in which the first composition and the second composition are simultaneously extruded or sequentially extruded, and a second composition layer obtained using the second composition is laminated on a first composition layer obtained using the first composition. Furthermore, there can be mentioned a lamination method in which the first composition is wound around an iron core to form a first composition layer, and the second composition is then wound thereon to form a second composition layer.
[0118] The precursor laminate may have a first composition layer, a second composition layer disposed on the first composition layer, and other layers. Details of the other layers are as explained in the method for producing the laminate, and therefore explanations thereof are omitted.
[0119] In the method for producing a precursor laminate of the present invention, the first composition and the second composition may be heated, preferably at a temperature that does not crosslink the polymers contained in each composition.
[0120] The first composition used to form the first composition layer contains a fluorine-containing copolymer A1 and a crosslinking agent, and may optionally contain a non-fluorine-containing polymer A2 and other components. Details of each component contained in the first composition are similar to those of each component contained in the first composition layer, and therefore description thereof will be omitted. The contents of each component in the first composition are the same as those in the first composition layer, and therefore description thereof will be omitted.
[0121] The second composition used to form the second composition layer contains a fluorinated copolymer B1 and a crosslinking agent, and may optionally contain a non-fluorinated polymer B2 and other components. Details of each component contained in the second composition are similar to those of each component contained in the second composition layer, and therefore description thereof will be omitted. The contents of each component in the second composition are the same as those in the second composition layer, and therefore the explanation thereof will be omitted. EXAMPLES
[0122] The present invention will be described in detail below with reference to examples. Examples 1 to 8 and 11 are working examples, and Examples 9 to 10 are comparative examples. Examples 12 and 13 are reference examples relating to chemical resistance (resistance to basic compounds). However, the present invention is not limited to these examples. The blending amount of each component in the tables below is based on mass.
[0123] <Measurement method> (Polymerization Composition of Fluorine-Containing Copolymer) The ratio (mol%) of each unit constituting the fluorine-containing copolymer is 19 The content was determined by F-nuclear magnetic resonance (NMR) analysis, fluorine content analysis, and infrared absorption spectroscopy.
[0124] (Iodine content of fluorine-containing copolymer) The iodine content of the fluorine-containing copolymer was determined using an automatic sample combustion apparatus, a pretreatment apparatus for ion chromatography (Mitsubishi Chemical Analytech Co., Ltd., AQF-100 model) in combination with an ion chromatograph.
[0125] (Storage shear modulus G' of fluorocopolymer) Using a rubber processing analyzer (RPA-2000, manufactured by Alpha Technologies), measurements were performed in accordance with ASTM D5289 and D6204 at a temperature of 100° C., an amplitude of 0.5 degrees, and a vibration frequency of 50 times / min.
[0126] (Mooney Viscosity of Fluorine-Containing Copolymer) Measurements were taken using a Mooney Viscometer (Shimadzu Corporation, SMV-201) in accordance with JIS K6300-1:2013, using an L-shaped rotor with a diameter of 38.1 mm and a thickness of 5.54 mm, at 100°C with a preheating time of 1 minute and a rotor rotation time of 4 minutes.
[0127] (Crosslinked content) The content of the crosslinked product of the fluorine-containing copolymer and the content of the crosslinked product of the non-fluorine-containing polymer in each crosslinked layer were determined as follows. First, the mass of the precursor laminate and the mass of the laminate after crosslinking were measured to confirm that there was no loss of mass. The contents of the fluorine-containing copolymer and the non-fluorine-containing polymer in the precursor laminate were determined as the contents of the crosslinked product of the fluorine-containing copolymer and the crosslinked product of the non-fluorine-containing polymer in each crosslinked layer, assuming that all the fluorine-containing copolymers were crosslinked products of the fluorine-containing copolymer and all the non-fluorine-containing polymers were crosslinked products of the non-fluorine-containing polymer.
[0128] <Ingredients> Fluorine-containing copolymer 1: Tecnoflon P757, manufactured by Solvay, a fluorine-containing copolymer having VdF units, TFE units and HFP units, the proportion of fluorine atoms in the copolymer being 67 mass%, and Mooney viscosity at 121° C. being 45. Fluorine-containing copolymer 1 contains iodine atoms. Fluorine-containing copolymer 2: Fluorine-containing copolymer having TFE units and propylene units, the ratio of TFE units to the total of all units constituting the copolymer is 56 mol %, the ratio of propylene units is 44 mol %, G'=250 kPa, Mooney viscosity=85, and contains 0.4 mass % of iodine atoms to the total mass of fluorine-containing copolymer 2. Fluorine-containing copolymer 2 was produced by the method disclosed in WO 2009 / 119202. Fluorine-containing copolymer 3: AFLAS (registered trademark) 150P, manufactured by AGC, a fluorine-containing copolymer having TFE units and propylene units and not containing iodine atoms or bromine atoms, G'=220 kPa, Mooney viscosity=95.
[0129] Non-fluorinated polymer 1: VAMAC® DP, manufactured by ChemoursDupont, ethylene-acrylic acid ester copolymer Non-fluorinated polymer 2: Esprene (registered trademark) E 501A, manufactured by Sumitomo Chemical Co., Ltd., ethylene-propylene-diene copolymer
[0130] Perhexa (registered trademark) 25B: crosslinking agent, organic peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, manufactured by NOF Corporation ParkerDox (registered trademark) 14: Crosslinking agent, organic peroxide, α,α'-bis-(tert-butylperoxy)diisopropylbenzene, manufactured by Kayaku Akzo Co., Ltd.
[0131] TAIC (registered trademark): crosslinking coagent, triallyl isocyanurate, 1,3,5-triallyl isocyanurate, manufactured by Mitsubishi Chemical Corporation
[0132] Calcium stearate: Acid acceptor, Fujifilm Wako Pure Chemical Industries, Ltd. o-Phenylphenol: Scorch retarder, Fujifilm Wako Pure Chemical Industries, Ltd. THENMAX® N-990: Reinforcement, Carbon Black, MT, Canarb Limited Kyowamag (registered trademark) MF-150: Acid acceptor, magnesium oxide, manufactured by Kyowa Chemical Industry Co., Ltd. Zinc oxide: acid acceptor, manufactured by Seido Chemical Co., Ltd.
[0133] Celite® 350: Sintered diatomaceous earth, manufactured by Celite Corporation AEROSIL® 300: hydrophilic silica, manufactured by Japan Aerosil Co., Ltd.
[0134] <Preparation of the first composition and the second composition> The ingredients were mixed uniformly in the mass ratios shown in Tables 1 and 2 using a two-roll mill to prepare first compositions a1 to a5 and second compositions b1 to b5, respectively.
[0135] [Table 1]
[0136] In Table 1, "content of fluorine-containing copolymer in total polymer" means the content (mass%) of fluorine-containing copolymer relative to the total of fluorine-containing copolymer and non-fluorine-containing polymer contained in the composition. The value of "content of fluorine-containing copolymer in total polymer" is the content of crosslinked product of fluorine-containing copolymer relative to the total of crosslinked product of fluorine-containing copolymer and crosslinked product of non-fluorine-containing polymer in the first crosslinked layer (the above-mentioned M CA ) and the content of the fluorine-containing copolymer relative to the total amount of the fluorine-containing copolymer and the non-fluorine-containing polymer in the first composition layer (the above-mentioned M PA ) was the same as In Table 1, "content of fluorocopolymer in composition" means the content (% by mass) of fluorocopolymer relative to the total mass of the composition. The value of "content of fluorocopolymer in composition" was the same as the content (% by mass) of the crosslinked product of fluorocopolymer in the first crosslinked layer, and the same as the content (% by mass) of fluorocopolymer in the first composition layer.
[0137] [Table 2]
[0138] In Table 2, "content of fluorine-containing copolymer in total polymer" means the content (mass%) of fluorine-containing copolymer relative to the total of fluorine-containing copolymer and non-fluorine-containing polymer contained in the composition. The value of "content of fluorine-containing copolymer in total polymer" is the content of the crosslinked product of fluorine-containing copolymer relative to the total of the crosslinked product of fluorine-containing copolymer and the crosslinked product of non-fluorine-containing polymer in the second crosslinked layer (the above-mentioned M CB ) and the content of the fluorine-containing copolymer relative to the total amount of the fluorine-containing copolymer and the non-fluorine-containing polymer in the second composition layer (the above-mentioned M PB ) was the same as In Table 2, "content of fluorocopolymer in composition" means the content (% by mass) of fluorocopolymer relative to the total mass of the composition. The value of "content of fluorocopolymer in composition" was the same as the content (% by mass) of the crosslinked product of fluorocopolymer contained in the second crosslinked layer, and was the same as the content (% by mass) of fluorocopolymer in the second composition.
[0139] [Examples 1-11] Laminates were produced using the first composition and the second composition in the combinations shown in Table 3, and were evaluated by the tests described below.
[0140] <Dimensional stability and warpage evaluation> (Preparation of laminate (test piece) for evaluation) Test pieces for evaluating dimensional stability were prepared according to the following procedure. First, the first composition and the second composition were each molded to a length of 120 mm × width of 105 mm × thickness of 1.3 mm, and laminated in the combinations shown in Table 3. This resulted in a precursor laminate including a first composition layer that was a molded body of the first composition, and a second composition layer that was disposed on the first composition layer and was a molded body of the second composition. The precursor laminate was placed in a mold and held at 170°C for 15 minutes under a pressure of 100 kgf (=9.8 MPa) for crosslinking to obtain each of the laminates of Examples 1 to 11. The dimensions of each of the obtained laminates were 130 mm long x 120 mm wide x 2 mm thick. The obtained laminate was punched out with a No. 3 dumbbell in accordance with JIS K6251: 2004. A hole with a diameter of 5 mm was made 1 cm away from the edge to obtain a test specimen for evaluation.
[0141] (Verification of dimensional stability and warping after heating) In order to maintain the performance of the device in which the laminate is incorporated, it is necessary to keep the dimensional change of the laminate within a certain range. Therefore, as an index of heat resistance, the dimensional stability and warping of the laminate after heating were confirmed. First, the length of the test piece before heating was measured. Note that the test piece before heating was not bent and was parallel to a flat surface when the test piece was placed on the surface. The hole in the test piece was hung on a metal hook, and the test piece hanging from the hook was placed in a hot air precision oven (manufactured by Yamato Scientific Co., Ltd.) heated to 240°C and heated. After 264 hours, the sample was removed from the oven. The heated test piece was air-cooled until it could be touched with bare hands. The length of the test piece after heating was measured, and the length of the test piece after heating was taken as the dimensional retention rate, assuming the length of the test piece before heating to be 100. The results are shown in Table 3. The closer the dimensional retention rate value is to 100, the more excellent the dimensional stability after heating is. In addition, when the heated test piece was placed on a flat surface, the angle between the flat surface and the test piece was measured. The results are shown in Table 3. When the test piece was placed on a flat surface, if it was parallel to the surface, it was 0°, and if it was bent perpendicularly, it was 90°. The closer the angle was to 0°, the less the laminate warped after heating.
[0142] <Evaluation of Adhesion> (Preparation of laminate (test piece) for evaluation) The test pieces used in the peel test were prepared by the following procedure. First, the first composition and the second composition were each molded to a length of 120 mm × width of 105 mm × thickness of 1.3 mm, and laminated in the combination shown in Table 3. This resulted in a precursor laminate including a first composition layer, which is a molded body of the first composition, and a second composition layer, which is a molded body of the second composition and is disposed on the first composition layer. When the precursor laminate was crosslinked to obtain a laminate, a release film was sandwiched between the first composition and the second composition when laminating the first composition layer and the second composition layer so that 1 / 4 of the laminate from the end of the long side in the width direction was a gripping portion that was not bonded. The precursor laminate with the release film sandwiched therebetween was placed in a mold and held for 15 minutes at 170°C under a pressure of 100 kgf (=9.8 MPa) in a heat press to carry out crosslinking, thereby obtaining each of the laminates of Examples 1 to 11. The dimensions of each of the obtained laminates were length 130 mm × width 120 mm × thickness 2 mm. The obtained laminate was cut in the width direction to obtain test pieces having a length of 120 mm, a width of 25 mm, and a thickness of 2 mm, and a gripping portion in which 40 mm from the end of the short side in the length direction was not bonded. The peel test described later was performed on four test pieces.
[0143] (peel test) For the test pieces prepared from the laminates of Examples 1 to 11, a T-peel test (JIS K6854-3:1999) was carried out. The gripped portion of each of the test pieces in Examples 1 to 11 was set in a T-type peel tester, and the first crosslinked layer and the second crosslinked layer of each of the test pieces were peeled off at a speed of 50 mm per minute at temperatures of 25° C. and 150° C. to measure the maximum peel strength between the first crosslinked layer and the second crosslinked layer. The results are shown in Table 3. The higher the peel strength, the better the adhesion between the first crosslinked layer and the second crosslinked layer.
[0144] <Evaluation of low temperature resistance> (Low temperature resistance test) The adhesion (presence or absence of peeling) at low temperatures was confirmed using a low-temperature elastic recovery tester, commonly known as a TR tester (manufactured by Yasuda Seiki Seisakusho). A laminate was prepared in the same manner as the test pieces for evaluating dimensional stability and warpage, and the obtained laminate was cut to obtain test pieces with a length of 65 mm, a width of 6 mm, and a thickness of 2 mm. The test piece was set in the sample holder in the TR tester and stretched by 10%. The test piece stretched by 10% was immersed together with the sample holder in a tank containing ethanol at -40°C and left to stand for 10 minutes. After 10 minutes, the temperature was raised at a rate of 1°C / min, and when it reached 25°C, the temperature increase was stopped. The test piece was removed and checked for the presence or absence of peeling by visual inspection and by pulling it lightly with the hand.
[0145] [Table 3]
[0146] It was confirmed that the laminates of Examples 1 to 8 and 11 obtained using the first composition and the second composition containing 85 mass % or more of a fluorinated copolymer based on the total amount of the fluorinated copolymer and the non-fluorinated polymer had good dimensional stability even after being kept at 240°C for 264 hours. The laminates of Examples 9 and 10 obtained using the first composition and the second composition containing less than 85 mass% of a fluorinated copolymer based on the total mass of the fluorinated copolymer and the non-fluorinated polymer had low dimensional stability after being kept at 240°C for 264 hours. It was confirmed that the laminates of Examples 1 to 6 and 11 obtained using the first composition and the second composition not containing a non-fluoropolymer showed little warping even after being kept at 240° C. for 264 hours. The laminates of Examples 5 and 6, which had a first composition layer containing the fluorine-containing copolymer 1, silica and celite, and a second composition layer containing a fluorine-containing copolymer having iodine atoms, also had excellent interlayer adhesion at 25°C and 150°C.
[0147] [Examples 12 and 13] <Evaluation of chemical resistance> Using a TAF-SR type PTFE cylindrical sealed container (manufactured by Taiatsu Glass Industries Co., Ltd.) with a heat resistance of 180°C, a pressure resistance of 7.5 MPa, and an internal volume of 300 cc, the test pieces were immersed in sodium hydroxide, ammonia, or ethylenediamine (hereinafter also referred to as "chemical solutions") to examine their chemical resistance (resistance to basic compounds).
[0148] (Preparation of test specimens) The test pieces used in the chemical resistance test were prepared as follows: The compositions shown in Table 4 were molded into 2 mm pieces, and crosslinked by holding them in a hot press at 170°C for 15 minutes at a pressure of 100 kgf (=9.8 MPa), and the crosslinked product was punched out with a No. 3 dumbbell according to JIS K6251:2004 to obtain four test pieces for measuring tensile strength, tensile elongation, and hardness. In addition, the compositions shown in Table 4 were crosslinked to obtain O-rings conforming to P26 of JIS B 2401-1:2012, and the resulting O-rings were used as test pieces for measuring the volume.
[0149] The test pieces before immersion in the chemical solution were measured for tensile strength, tensile elongation, hardness, and volume. The tensile strength and tensile elongation of the above-mentioned No. 3 dumbbell were measured in accordance with JIS K6251: 2017. A tensile tester with data processing (Quick Reader TS-2530, manufactured by Ueshima Seisakusho Co., Ltd.) was used as the measuring device. The hardness (Shore-A) of the No. 3 dumbbells was measured in accordance with JIS K6253-3:2012. An automatic rubber hardness tester (Digitest Shore A, manufactured by H. Burleith Testing Instruments) was used as the measuring device. Three No. 3 dumbbells were stacked to a total height of 6 mm, which was then placed on the measuring device and the hardness was measured. The volume of the above-mentioned O-ring test piece was measured using a specific gravity meter (DMA-220, manufactured by Shinko Denshi Co., Ltd.) as a measuring device.
[0150] Three No. 3 dumbbell test pieces other than those used to measure tensile strength, tensile elongation, and hardness, and the test piece used to measure the volume were placed in the above-mentioned sealed container, and then 50% sodium hydroxide aqueous solution, 28% ammonia aqueous solution, or ethylenediamine was added. The container was then covered with a lid and completely sealed using a vice. The sealed container was placed in an oven set at 70°C and left to stand for 720 hours. After 720 hours, the specimen was removed from the oven, cooled to below 35°C, and the lid of the sealed container was opened. The specimen was removed and the chemical solution adhering to the specimen was washed with water. The specimen was placed on a water-absorbent cloth, and the water droplets on the surface were quickly removed. For the ethylenediamine test only, the sealed container was placed in an oven set at 25°C and left to stand for 144 hours. After 144 hours, it was removed from the oven, the test piece was taken out, and the chemical solution adhering to the test piece was washed with water. It was then placed on a water-absorbent cloth and the water droplets on the surface were quickly removed.
[0151] The tensile strength, tensile elongation, and hardness of the three No. 3 dumbbell test pieces after immersion in the chemical solution were measured. The measurement method was the same as that of the test piece before immersion in the chemical solution. The arithmetic average of the measured values of the three test pieces was recorded. The volume of the O-ring test piece after immersion in the chemical solution was measured in the same manner as for the test piece before immersion in the chemical solution.
[0152] 100 + [(tensile strength of the test piece after immersion in the chemical solution) - (tensile strength of the test piece before immersion in the chemical solution)] / (tensile strength of the test piece before immersion in the chemical solution) × 100 is the tensile strength retention rate (%). 100 + [(tensile elongation of the test piece after immersion in the chemical solution - (tensile elongation of the test piece before immersion in the chemical solution))] / (tensile elongation of the test piece before immersion in the chemical solution) × 100 is the tensile elongation retention rate (%), (Hardness of the test piece before immersion in the chemical solution) - (Hardness of the test piece after immersion in the chemical solution) is the hardness change degree, The volume change rate (%) was calculated as [(volume of the test piece after immersion in the chemical solution) - volume of the test piece before immersion in the chemical solution)] / (volume of the test piece before immersion in the chemical solution) × 100. The results are shown in Table 4.
[0153] [Table 4]
[0154] As shown in Table 4, the crosslinked product of composition b4 showed good physical properties even after immersion in a basic chemical solution. Therefore, when the laminate of the present invention is used in such a manner that the second crosslinked layer side containing the crosslinked product of the fluorine-containing copolymer having TFE units and propylene units comes into contact with a basic chemical solution, it is expected that the laminate will have excellent chemical resistance (resistance to basic compounds). Moreover, the crosslinked product of composition a1 was greatly deformed or destroyed when immersed in a basic chemical solution. Therefore, it is expected that the laminate of the present invention will have excellent chemical resistance (resistance to basic compounds) if it is used in such a manner that the second crosslinked layer side containing the crosslinked product of the fluorocopolymer having TFE units and propylene units contacts the basic chemical solution and the first crosslinked layer side containing the crosslinked product of the fluorocopolymer having VDF units does not contact the basic chemical solution.
Claims
1. A laminate having a first crosslinked layer and a second crosslinked layer disposed on the first crosslinked layer, the first crosslinked layer contains a crosslinked product of a fluorinated copolymer A1 and optionally contains a crosslinked product of a non-fluorinated polymer A2; the second crosslinked layer comprises a crosslinked product of a fluorine-containing copolymer B1 and optionally a crosslinked product of a non-fluorine-containing polymer B2; a combination of units based on monomers constituting the fluorocopolymer A1 and a combination of units based on monomers constituting the fluorocopolymer B1 are different from each other, The content M of the crosslinked product of the fluorocopolymer A1 relative to the total of the crosslinked product of the fluorocopolymer A1 and the crosslinked product of the non-fluoropolymer A2 CA is 85% by mass or more, The content M of the crosslinked product of the fluorocopolymer B1 relative to the total of the crosslinked product of the fluorocopolymer B1 and the crosslinked product of the non-fluoropolymer B2 CB is 85% by mass or more.
2. Said M CA and the above M CB The laminate according to claim 1 , wherein the absolute value of the difference between the above and the above is 15 mass % or less.
3. The fluorine-containing copolymer A1 contains units based on vinylidene fluoride, The laminate according to claim 1 or 2, wherein the fluorine-containing copolymer B1 contains units based on tetrafluoroethylene and units based on propylene.
4. The laminate according to any one of claims 1 to 3, wherein at least one of the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom.
5. The laminate according to any one of claims 1 to 4, wherein the glass transition temperatures of said fluorocopolymer A1 and said fluorocopolymer B1 are both 15°C or lower.
6. The laminate according to any one of claims 1 to 5, wherein at least one of the first crosslinked layer and the second crosslinked layer further contains a sintered body of diatomaceous earth and silica.
7. the first crosslinked layer does not contain a crosslinked product of the non-fluorinated polymer A2, The laminate according to any one of claims 1 to 6, wherein the second crosslinked layer does not contain a crosslinked product of the non-fluorinated polymer B2.
8. A precursor laminate having a first composition layer and a second composition layer disposed on the first composition layer, The first composition layer contains a fluorine-containing copolymer A1 and a crosslinking agent, and optionally contains a non-fluorine-containing polymer A2, The second composition layer contains a fluorine-containing copolymer B1 and a crosslinking agent, and optionally contains a non-fluorine-containing polymer B2, a combination of units based on monomers constituting the fluorocopolymer A1 and a combination of units based on monomers constituting the fluorocopolymer B1 are different from each other, The content M of the fluorine-containing copolymer A1 relative to the total of the fluorine-containing copolymer A1 and the non-fluorine-containing polymer A2 PA is 85% by mass or more, The content M of the fluorine-containing copolymer B1 relative to the total of the fluorine-containing copolymer B1 and the non-fluorine-containing polymer B2 PB is 85 mass % or more.
9. Said M PA and the above M PB The precursor laminate according to claim 8 , wherein the absolute value of the difference between the above and the above is 15 mass % or less.
10. The fluorine-containing copolymer A1 contains units based on vinylidene fluoride, The precursor laminate according to claim 8 or 9, wherein the fluorine-containing copolymer B1 contains units based on tetrafluoroethylene and units based on propylene.
11. The precursor laminate according to any one of claims 8 to 10, wherein at least one of the fluorine-containing copolymer A1 and the fluorine-containing copolymer B1 has at least one of an iodine atom and a bromine atom.
12. The precursor laminate according to any one of claims 8 to 11, wherein the glass transition temperatures of the fluorocopolymer A1 and the fluorocopolymer B1 are both 15°C or lower.
13. The precursor laminate according to any one of claims 8 to 12, wherein at least one of the first composition layer and the second composition layer further contains a sintered body of diatomaceous earth and silica.
14. The first composition layer does not contain the non-fluorinated polymer A2, The precursor laminate according to any one of claims 8 to 13, wherein the second composition layer does not contain the non-fluorinated polymer B2.
Citation Information
Patent Citations
Rubber laminate and uses thereof
WO1998036901A1